Die Hungerunruhen in Hamburg im Juni 1919 - eine zweite Revolution? - Schulte-Varendorff, Uwe (Beiträge zur Geschichte Hamburgs, 2010)
With the end of the First World War, the defeat of the German Empire, was sealed in November 1918. Even after the end of the subsequent revolutionary phase, political conditions in Hamburg remain unstable. On the one hand, they were marked by militant clashes between radical groups; on the other hand, hunger and misery continued to dominate the everyday life of the population. This was the breeding ground for a short section of the history of the Free and Hanseatic City of Hamburg, which had not received much attention so far: the "Aspic Riots" or "Hunger Riots" (Sülze- oder Hungerunruhen) .They broke out in the city at the end of June 1919.The discovery of scandalous production and processing methods of a jelly manufacturer led to turmoil throughout the city. These civil war-like conditions, which lasted only a few days, were the reason for the invasion of the Reichswehr troops under General Paul von Lettow-Vorbeck. The background, process and effects of the "hunger riots" are examined and presented in this paper.